Ecological state of Severnaya Bight (Slavianka Bay, Peter the Great Bay, Japan Sea) - V. A. Luchin; N. I. Grigoryeva (Известия ТИНРО, 2018)
Oceanographic and chemical properties, sea currents, bottom topography and sediments in the Severnaya Bight (Slavianka Bay of Peter the Great Bay, Japan Sea) are considered on the base of all available data collected from 1965 to 2018. Mean and extreme values of the water parameters in the bight are determined for the first time. Seasonal and short-term tide-induced variations of the water temperature and salinity at certain depths are described. The environments influence on aquaculture is estimated. The hanging culture equipment can be mounted in the bight at the depth of no less than 10–12 m, whereas the bottom culture is possible in local areas with the depth of 6–10 m located in its northern and northwestern parts and southwestward from the Mininosok Inlet. In the north of the bight, the cultivated scallop is subjected to unfavorable influence of high water temperature and low salinity, but the water regime at the depth of 6–8 m, where the collectors and hatcheries are usually mounted, is relatively stable and favorable for the scallop cultivation, with rather rare and short-term rises of temperature (up to 25 °С), declines of salinity (to 24 ‰), and dissolved oxygen depletion (to 3.17 mL/L, or 58 %). Currents in the Severnaya Bight are strong enough for its waters renewal: 25–30 cm/s. The currents are almost reverse in the top of the bight; the semi-permanent cyclonic circulation develops in its main part that provides the water exchange with the open part of Peter the Great Bay and distribution of suspended solids, contaminants, bacteria, or larvae from marine farms or other sources over the bight. The non-tidal currents are almost twice stronger in winter than in summer.